Motivation to Use Gamification Elements in E-Learning for Formal and Non-Formal Education - Afirando, Rio; Santoso, Harry Budi; Junus, Kasiyah; Putra, Panca O. Hadi; Lawanto, Oenardi (AI Society & STMIK Indonesia, 2023)
The implementation of gamification in e-learning is not new, both within the context of formal and informal. Formal education is a learning activity organized by both public and private parties that refers to the official education system of a country. Meanwhile, informal education is another learning activity that does not refer to the official education system of a country. Not only visually appealing, but gamification elements also have a certain motivation and emotional value for the user. This study seeks to compare the use of gamification elements and their motivation between formal and nonformal education. The method used was a Systematic Literature Review using the Kitchenham method. From the selected databases, 65 articles were obtained that had implemented gamification in e-learning. The gamification elements were grouped by motivation and emotion based on the Octalysis framework. The results showed that ownership and possession were the most prominent motivations for implementing gamification.